2010
DOI: 10.1007/s12289-010-0827-8
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating Flow in Capillary Dies for a Hdpe Melt: Effects of Extrusion Parameters

Abstract: The study of the instability phenomena of polymer melts in capillary flows is of great technical relevance since, during an industrial die forming operation, these instabilities can give origin to a transition from a defect-free to a highly-defective extrudate. In this work, the instability phenomena exhibited in capillary flow by a blow moulding grade of high-density polyethylene (HDPE) were analyzed. In particular, by means of a capillary rheometer, which mimics polymer extrusion, the effects of specific ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(14 reference statements)
3
1
0
Order By: Relevance
“…This result indicates that, at a given temperature, the piston velocity has an influence on the kinetics of the processes responsible for the achievement of the hydrodynamic boundary conditions able to give rise to the macrofracture of the flow; by contrast, as outlined above, the critical levels of pressure involved ( P o,min and P o,max ) are practically piston velocity independent. This was already observed by the authors for an unfilled HDPE with molecular mass distribution broader than the HDPE object of this study , and it is confirmed also for melts filled with glass beads or fibers. Interestingly, it can be observed from Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This result indicates that, at a given temperature, the piston velocity has an influence on the kinetics of the processes responsible for the achievement of the hydrodynamic boundary conditions able to give rise to the macrofracture of the flow; by contrast, as outlined above, the critical levels of pressure involved ( P o,min and P o,max ) are practically piston velocity independent. This was already observed by the authors for an unfilled HDPE with molecular mass distribution broader than the HDPE object of this study , and it is confirmed also for melts filled with glass beads or fibers. Interestingly, it can be observed from Fig.…”
Section: Resultssupporting
confidence: 89%
“…It comes out also that, for each material, both v p,stick‐slip,min and v p,stick‐slip,max increase by increasing the process temperature. This, for the unfilled HDPE melt, was expected on the basis of the results obtained by the authors in a previous work . Although the piston velocities at the extremes of the “stick‐slip” region generally increased with the process temperature for the unfilled and the filled melts, the temperature effects were more contained for the latter melts than for the former.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In the work of Baldi, the effects of extrusion parameters (temperature and imposed flow rate) on the oscillating flow exhibited by a HDPE melt were analyzed by capillary rheometry. All the tests were performed using a fixed die geometry (Baldi, F., Franceschini, A., Briatico-Vangosa, F., Locati, D. and Riccò, 2010). The results put in evidence that the imposed flow rate (piston speed) has an influence on the kinetics of the processes that govern the oscillating flow but not on the extrusion pressure levels characteristic of the instabilities, which are strongly dependent, in a complex way, only on the temperature.…”
Section: Introductionmentioning
confidence: 99%